Building a yardstick–a benchmark framework for assessing higher education management institutions. Issue 8 (9th February 2021) - Palaniappan, Umayal; Suganthi, L.; Shagirbasha, Shameem
Abstract : Purpose: Higher education management institutions play a vibrant role in imparting managerial skills to the students to face the corporate world. Performance evaluation of such institutions is mandate to ensure the outcome quality. To establish this, the present research explored the critical performance indicators of management institutions using the balanced scorecard (BSC) approach. Design/methodology/approach: This research explored the critical performance indicators of public, private and standalone management institutions in India. Data were collected from the representative sample of all the stakeholders in those management institutions. A specific vision was created and a systematic procedure was employed to arrive at the objectives, measures and metrics of the scorecard specific to the vision. Confirmatory factor analysis was used to perform analysis on the collected data. For the objectives and measures that evolved from confirmatory factor analysis, metrics were formulated based on the expert opinion. Findings: The study resulted in 16 objectives, 46 measures and 54 metrics encompassing all the four perspectives of BSC. This paper has contributed a concrete, concise, comprehensive and context specific framework. Research limitations/implications: The nature of the BSC framework paves the way for continuous assessment and eventually helps the institutions to attain sustainable growth. This research contributes to the literature of balanced scorecard and also to the performance assessment of the management institutions. Originality/value: BSC-based benchmarking is a unique contribution to the academia of management education to precisely measure the performance of institutions. The model comprehensively includes the indicators from all the perspectives of stakeholders in terms of objectives, measures and metrics, thus proposing a holistic assessment.